Computational Thinking in Developing Students’ Reading Comprehension Skill - Amalia, Puji Astuti; Kurniawan , Andri; Fahmimroah, Feti; Arditiya, Arditiya (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Understanding and interpreting text is a crucial component of reading comprehension. This process might be hampered by several problems, which affect students' capacity to understand meaning. However, there are several strategies that can be applied regarding this issue. The first is using appropriate reading techniques, especially computational thinking. And the second is using visual aid. Students' understanding can be improved by using visual aids like graphic organizers or pictures to help them visualize ideas and relationships in the text. The purpose of this study was to produce a story mapping card as a visual aid that can help students understand English texts better. The development was carried out through the method of formulating problems, collecting data, designing products, validating designs, revising designs, conducting trials, drawing conclusions. The results of the study showed that the story mapping card was valid and ready to use. The results of the assessment of the story mapping card were an average of 4.5 with a very good category, the indicator of the benefits of the story mapping card for students got a total average value of 4.5 with a very good category and the indicator of ease of use of the story mapping card in the reading stage for teachers with a total average value of 4.4 with a very good category.